Model of Institutional Management in Small Islands of Bunaken Nasional Park - Tangian, Diane; Polii, Bernadain Dainty (Journal of Indonesian Tourism and Development Studies, 2017)
Bunaken National Park is a conservation area that has the beauty and underwater tourist attraction, which is the mainstay of tourism in North Sulawesi. Its beauty and appeal attract both domestic and foreign tourists to visit this region. Economically it is a positive impact on improving the economy and welfare of the community, but on the other hand, it has a negative impact on the quality of the local environment. It is characterized by the decline in coral cover area, caused by tourism activity itself. Utilization of natural resources as objects and tourist attraction should be done carefully, taking into account the balance of ecological, socio-economic and socio-cultural aspects. The concept of ecotourism is a concept that takes into account the balance of these three aspects, for the TNB travel management needs to be done based on the concept of ecotourism. Model TNB travel management institutions use the systems approach to the Interpretative Structural Modeling (ISM) method. This method is carried out to see the degree of interest among the elements involved in the management of Bunaken National Parks with reference to the expert opinion. Results obtained show that the goals are to protect coral reef ecosystems as objects and tourist attraction, the institutions involved are the Board of Bunaken National Park, a strategic program that is required is to set the number of tourist visits, and furthermore that a major constraint program is the lack of commitment the actors involved. Keywords: Ecotourism, sustainable management, model, ISM, the conservation area.